Sichuan dark tea improves lipid metabolism and prevents aortic lipid deposition in diet-induced atherosclerosis model rats - Lu, Rui; Sugimoto, Takumi; Tsuboi, Tomoe; Sekikawa, Tatsushi; Tanaka, Mamoru; Lyu, Xiaohua; Yokoyama, Shinji (Frontiers in Nutrition, 2022)
Background and aims Sichuan dark tea (ST), Zangcha, is a traditional fermented Chinese tea found in Sichuan and Tibet and claimed for beneficial effects against lifestyle-related metabolic disorders. We examined the effects of ST on lipid metabolism and atherosclerosis. Methods and results Sichuan dark tea was given to fat-rich diet-induced atherosclerosis model rats in comparison with dark-fermented Chinese Pu-erh tea (PT) and Japanese green tea (GT). After 8 weeks of feeding, ST and PT induced an increase in high-density lipoprotein (HDL)-cholesterol and a decrease in glucose, and ST decreased triglyceride in plasma. ST also induced low pH in the cecum. There was no significant change in their body weight among the fat-feeding groups but a decrease was found in the visceral fat and liver weight in the ST group. Accordingly, ST reduced lipid deposition in the aorta in comparison with PT and GT. ST increased mRNA of LXRα, PPARα, PPARγ, and ABCA1 in the rat liver. The extract of ST stimulated the AMPK pathway to increase the expression of ABCA1 in J774 cells and increased expression of lipoprotein lipase and hormone-sensitive lipase in 3T3L1 cells, consistent with its anti-atherogenic effects in rats. High-performance liquid chromatography analysis showed unique spectra of original specific compounds of caffeine and catechins in each tea extract, but none of them was likely responsible for these effects. Conclusion Sichuan dark tea increases plasma HDL and reduces plasma triglyceride to decrease atherosclerosis through AMPK activation. Further study is required to identify specific components for the effects of this tea preparation.